Flipping Houses For Dummies - Roberts, Ralph R. (Wiley, 2014)
Not just another house flipping book You can find plenty of books about flipping houses that claim "anyone can do it." Flipping Houses For Dummies takes a different approach-honesty. We don't claim that flipping houses is "easy" or "simple" or "risk-free," because, quite frankly, it isn't. Flipping Houses For Dummies reveals the risks and rewards of flipping properties; helps you determine whether you have the time, energy, cash, and other resources to be successful; and then conveys the expert knowledge that those who wish to pursue house flipping need in order to minimize risk and maximize potential profits in a very competitive market. Negotiating strategies to close deals faster Mortgage myths in the new economy Time- and money-saving tips for making every day and every dollar count New strategies for scoring bank-owned and foreclosed properties Quick makeover solutions on everything from curb appeal to kitchens and bathrooms Flipping Houses For Dummies provides plenty of examples of successful and not-so-successful property flips, presenting the total investment (in time and money), the work involved, and the net profit. If you're ready for hard work and big profits, start flipping!
Description based on publisher supplied metadata and other sources
Keywords: House buying; House selling; Real estate development